2016
DOI: 10.3390/v8030077
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Viral Communities of Biting Midges and Identification of Novel Thogotovirus Species and Rhabdovirus Genus

Abstract: More than two thirds of emerging viruses are of zoonotic origin, and among them RNA viruses represent the majority. Ceratopogonidae (genus Culicoides) are well-known vectors of several viruses responsible for epizooties (bluetongue, epizootic haemorrhagic disease, etc.). They are also vectors of the only known virus infecting humans: the Oropouche virus. Female midges usually feed on a variety of hosts, leading to possible transmission of emerging viruses from animals to humans. In this context, we report here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Although the current International Committee on Taxonomy of Viruses (2015) (ICTV) (www.ictvonline.org/virustaxonomy.asp) only lists two species within the genus Thogotovirus , there are now actually eight viruses within the genus: Thogoto (THOV), Dhori (DHOV), Batken (BKNV), Upolu (UPOV), Aransas Bay (ABV), Jos (JOSV), Bourbon (BRBV) and Dielmo orthomyxovirus (DOV) (Allison et al, 2015, Bussetti et al, 2014, Lvov et al, 2015, Briese et al, 2014, Lambert et al, 2015, Temmam et al, 2016). The addition of SINUV to the genus will bring the total number of thogotoviruses to nine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the current International Committee on Taxonomy of Viruses (2015) (ICTV) (www.ictvonline.org/virustaxonomy.asp) only lists two species within the genus Thogotovirus , there are now actually eight viruses within the genus: Thogoto (THOV), Dhori (DHOV), Batken (BKNV), Upolu (UPOV), Aransas Bay (ABV), Jos (JOSV), Bourbon (BRBV) and Dielmo orthomyxovirus (DOV) (Allison et al, 2015, Bussetti et al, 2014, Lvov et al, 2015, Briese et al, 2014, Lambert et al, 2015, Temmam et al, 2016). The addition of SINUV to the genus will bring the total number of thogotoviruses to nine.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of SINUV to the genus will bring the total number of thogotoviruses to nine. Most of the thogotoviruses have been associated with ticks, although Batken virus has been isolated from both ticks and mosquitoes (Lvov et al, 1974), Sinu virus was isolated from mosquitoes and Dielmo orthomyxovirus was found in Culicoides midges (Temmam et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These partial genomic sequences belong to the same novel virus, which we named Lobeira virus (LOBV) ( Table 2 ). According to our phylogenetic tree based on L protein, this virus clustered with high node values with RISV, NOCRV and Tongilchon virus 1 forming clade I of the recently proposed Dielmovirus genus, dimarhabdovirus supergroup (dipteran-mammal-associated rhabdovirus) [ 36 ]. Together with clade II, clade I behaves as a basally rooted lineage of dimarhabdovirus supergroup ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Female midges feed on a variety of hosts, and therefore a diversity of plant, animal and human viruses can be identified in the virome [50]. They transmit various culicoides-borne arboviruses, e.g., Schmallenberg virus in European ruminants, Bluetongue virus, Oropouche virus and African horse sickness virus [51,52,53].…”
Section: Mosquitoes As “Flying Syringes” For Virus Surveillancementioning
confidence: 99%